The Reform of the Indonesian Competition Law to Anticipate ASEAN Economic Community - Siswanto, Ari -; Hutajulu, Marihot Janpieter (Faculty of Law, Padjadjaran University, 2018)
AbstractThis paper discusses the need to reform the Indonesian Competition Law (the Law Number 5 of 1999) due to the implementation of the ASEAN Economic Community (AEC), which undoubtedly influences the business condition in Indonesia. This study is expected to provide input for the revision of the Law Number 5 of 1999 by identifying the weaknesses of the current law. Accordingly, this paper aims to analyze the aspects of Indonesian Competition Law that are need to be reformed to ensure its capability in anticipating and regulating business competition after the implementation of AEC. This study found that the degree of the implementation of the Indonesian Competition Law is particularly specified in Article 1(e), which elucidates that the business actors to which the competition law applies are those who are âdidirikan dan berkedudukan dalam wilayah hukum Republik Indonesiaâ (established and domiciled within the jurisdiction of the Republic of Indonesia) or âmelakukan kegiatan dalam wilayah hukum negara Republik Indonesiaâ (to conduct activities within the territory of the Republic of Indonesia). The phrase âdalam wilayah hukum Republik Indonesiaâ (within the jurisdiction of the Republic of Indonesia) contained in Article 1(e) clearly indicates that the application of Indonesian Competition Law still relies heavily on the principle of territoriality. Therefore, the Indonesian Competition Law cannot reach business actors who are established, or are domiciled, or do conduct activities outside Indonesia, although they perform actions that affect the condition of business competition in Indonesia. Therefore, the Indonesian Competition Law needs to be reformed to enable its extra-territorial implementation based on the âeffects doctrineâ justifying the application of national law to any foreign business actors that causes the disruption of fair business competition conditions at the domestic level.AbstrakTulisan ini membahas tentang perlunya reformasi dalam Hukum Persaingan usaha Indonesia (UU No. 5 tahun 1999) berkenaan dengan pemberlakuan Masyarakat Ekonomi ASEAN (MEA) yang niscaya mempengaruhi kondisi persaingan usaha di Indonesia. Kajian ini diharapkan bisa memberikan masukan bagi upaya merevisi UU No. 5 Tahun 1999 dengan cara mengidentifikasi kelemahan-kelemahan yang ada di dalam Hukum Persaingan Usaha Indonesia dan perlu diperbaiki agar bisa mengantisipasi dan mengatur persaingan usaha yang dimunculkan oleh MEA. Studi ini mengemukakan bahwa cakupan keberlakuan Hukum Persaingan Usaha Indonesia terutama ditentukan dalam Pasal 1(e) UU No. 5 Tahun 1999 yang menjelaskan bahwa pelaku usaha yang dimaksud adalah pelaku usaha yang âdidirikan dan berkedudukan dalam wilayah hukum Republik Indonesiaâ atau âmelakukan kegiatan dalam wilayah hukum negara Republik Indonesia.â Frasa âdalam wilayah hukum Republik Indonesiaâ yang ada dalam Pasal 1(e) tersebut secara jelas menunjukkan bahwa penerapan Hukum Persaingan Usaha Indonesia masih sangat bergantung pada prinsip teritorialitas. Dengan begitu, Hukum Persaingan Usaha Indonesia tidak bisa menjangkau pelaku usaha yang didirikan di luar Indonesia, berkedudukan di luar Indonesia dan melakukan kegiatan di luar Indonesia, meski pelaku usaha itu melakukan tindakan yang berdampak pada kondisi persaingan usaha di Indonesia. Oleh sebab itu, Hukum Persaingan usaha Indonesia harus diperbaiki sedemikian rupa sehingga memungkinkan diterapkannya âdoktrin efekâ yang membenarkan penerapan hukum nasional terhadap pelaku usaha asing yang mengganggu kondisi persaingan sehat pada aras domestik.DOI: https://doi.org/10.22304/pjih.v5n2.a3